2000
DOI: 10.1093/molehr/6.2.146
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an immortalized human granulosa cell line (COV434)

Abstract: We have investigated the biological characteristics of an immortalized granulosa cell line (COV434), which may be used to study follicular and oocyte maturation in vitro. Granulosa cell function was defined as consisting of three distinct properties: (i) production of 17beta-oestradiol in response to follicle stimulating hormone (FSH); (ii) presence of specific molecular markers of apoptosis enabling the induction of follicular atresia; and (iii) capacity to form intercellular connections with cells surroundin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(90 citation statements)
references
References 35 publications
1
82
1
Order By: Relevance
“…The mouse TM3 and TM4 (Mather 1982), LbT2 (Pernasetti et al 2001), AC (Rilianawati et al 1998, Rahman et al 2001, Farnworth et al 2006b), COV434 (Zhang et al 2000) and KGN (Nishi et al 2001) cell lines were obtained as previously described (Farnworth et al 2006b, Chand et al 2007). Rats and mice were obtained from Central Animal House, Monash University (Clayton, Victoria, Australia).…”
Section: Methodsmentioning
confidence: 99%
“…The mouse TM3 and TM4 (Mather 1982), LbT2 (Pernasetti et al 2001), AC (Rilianawati et al 1998, Rahman et al 2001, Farnworth et al 2006b), COV434 (Zhang et al 2000) and KGN (Nishi et al 2001) cell lines were obtained as previously described (Farnworth et al 2006b, Chand et al 2007). Rats and mice were obtained from Central Animal House, Monash University (Clayton, Victoria, Australia).…”
Section: Methodsmentioning
confidence: 99%
“…We found that the COV434 cell line, established from a metastatic granulosa cell tumor removed from a 27-year-old female, 26,27 lacked the FOXL2 mutation and did not express the FOXL2 gene. This strongly suggests that the COV434 cell line is derived from a juvenile granulosa cell tumor.…”
mentioning
confidence: 88%
“…As the hGL cells have undergone a process of terminal differentiation in response to a luteinizing surge of gonadotropins, we wanted to characterize the effect of the purified rhBMP15 on granulosa cells which have not become terminally differentiated. An immortalized human granulosa cell line COV434 was chosen as it has retained the ability to produce estradiol upon FSH stimulation, thus demonstrating the presence of functional FSH receptors (Zhang et al 2000). The COV434 cells were transiently transfected with the Smad1/5/8 responsive transcriptional reporter construct, BRE-luciferase (Korchynskyi and ten Dijke 2002) and treated with the purified rhBMP15wt mature region, which activated BRE-luciferase reporter in a dose responsive manner (Fig.…”
Section: Human Bmp15 Produced By Hek-293t Cells Is Sensitive To C-termentioning
confidence: 99%